Synthesis of oligoesters plastic film from polylactic acid with mono ester plasticizer of wood flour and rice bran and its hydro degradation - Edwin Azwar (Jurnal Rekayasa Proses, 2014)
Composites of polylactic acid (PLA) with mono ester plasticizer (MEP) from wood flour and rice bran were prepared to evaluate the effect of MEP filler content on the mechanical, functional, thermal, and morphological properties of the composites and its degradation. The SEM study provided evidence that there was sufficient interfacial adhesion between the PLA matrix and the MEP from wood flour and rice bran filler. This was likely a result of mechanical interlocking among them. An addition of 10 and 30% MEP from wood flour or rice bran resulted in an improvement of strain and tensile properties of the composite. The composites of PLA and MEP from wood flour and rice bran experienced degradation through hydrolysis of regions that have crystalline structure.